Ceramic composites: A review of toughening mechanisms and demonstration of micropillar compression for interface property extraction. Issue 4 (24th January 2018) - Kabel, Joey; Hosemann, Peter; Zayachuk, Yevhen; Armstrong, David E. J.; Koyanagi, Takaaki; Katoh, Yutai; Deck, Christian
Abstract: Abstract : Ceramic fiber–matrix composites (CFMCs) are exciting materials for engineering applications in extreme environments. By integrating ceramic fibers within a ceramic matrix, CFMCs allow an intrinsically brittle material to exhibit sufficient structural toughness for use in gas turbines and nuclear reactors. Chemical stability under high temperature and irradiation coupled with high specific strength make these materials unique and increasingly popular in extreme settings. This paper first offers a review of the importance and growing body of research on fiber–matrix interfaces as they relate to composite toughening mechanisms. Second, micropillar compression is explored experimentally as a high-fidelity method for extracting interface properties compared with traditional fiber push-out testing. Three significant interface properties that govern composite toughening were extracted. For a 50-nm-pyrolytic carbon interface, the following were observed: a fracture energy release rate of ∼2.5 J/m 2, an internal friction coefficient of 0.25 ± 0.04, and a debond shear strength of 266 ± 24 MPa. This research supports micromechanical evaluations as a unique bridge between theoretical physics models for microcrack propagation and empirically driven finite element models for bulk CFMCs.